Concentrations of mercury in needles and leaves of different age - Pleijel, Håkan (University of Gothenburg, 2025)
The file contains data on concentrations of mercury in differently aged needles and leaves of four evergreen species: nine needle age classes for Picea abies, fourteen needle age classes for Abies pinsapo var. marocana, and three leaf age classes for both Trochodendron aralioides and Rhododendron catawbiense. For the two conifers, mercury concentrations are also given for the branch segments to which the different needle age classes were attached. The observations were made in Gothenburg, Sweden.

Filen innehåller data om koncentrationer av kvicksilver i olika gamla barr och blad av fyra städsegröna arter: nio barrårgångar för Picea abies, fjorton barrårgångar för Abies pinsapo var. marocana, tre bladårgångar vardera för Trochodendron aralioides och Rhododendron catawbiense. För de båda barrträden finns även data rörande kvicksilverkoncentrationen i de grensegment på vilka de olika barrårgångarna satt. Observationerna är gjorda i Göteborg.
Halter av kvicksilver i barr och blad av olika ålder
Keywords: leaf age; evergreen plants; ständigt gröna växter; conifers; barrträd; needles (parts of plants); barr; accumulation; ackumulation; mercury; kvicksilver; vegetation; vegetation; saturation; mättnad; forest; skog; Trochodendron aralioides; Abies pinsapo var. marocana; Rhododendron catawbiense; Picea abies; Geochemistry; Geokemi; Botany; Botanik